2014
DOI: 10.1051/0004-6361/201323099
|View full text |Cite
|
Sign up to set email alerts
|

Spitzerobservations of a circumstellar nebula around the candidate luminous blue variable MWC 930

Abstract: Context. The source MWC 930 is a star just ∼2 • above the Galactic plane whose nature is not clear and has not been studied in detail so far. While a post-asymptotic giant branch classification was proposed in the past, studies of its optical spectrum and photometry pointed toward strong variability, therefore, the object was reclassified as a luminous blue variable (LBV) candidate. Aims. The LBVs typically undergo phases of strong mass loss in the form of eruptions that can create shells of ejecta around the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
3
3
0
Order By: Relevance
“…These spectra are very similar to those of other dust-rich massive stars observed with Spitzer/IRS (e.g. the LBV and LBV candidates HR Car, HD 168625, G79.29+0.46, andMWC 930, Umana et al 2009, 2010;Agliozzo et al 2014;Cerrigone et al 2014).…”
Section: Dust Emission Distributionsupporting
confidence: 79%
See 1 more Smart Citation
“…These spectra are very similar to those of other dust-rich massive stars observed with Spitzer/IRS (e.g. the LBV and LBV candidates HR Car, HD 168625, G79.29+0.46, andMWC 930, Umana et al 2009, 2010;Agliozzo et al 2014;Cerrigone et al 2014).…”
Section: Dust Emission Distributionsupporting
confidence: 79%
“…These spectra are very similar to those of other dust-rich massive stars observed with Spitzer/IRS (e.g. the LBV and LBV candidates HR Car, HD 168625, G79.29+0.46, andMWC 930, Umana et al 2009, 2010;Agliozzo et al 2014;Cerrigone et al 2014). The spectra of the central stars in MB3955 and MB4121 are much poorer in terms of gas lines, with only a few emission lines detected towards both of them (see Figure 4 and Table 5).…”
Section: Dust Emission Distributionsupporting
confidence: 79%
“…As we discussed in [3], the presence of a far-IR excess in the spectral energy distribution of MWC 930 was a hint towards the LBV evolutionary status. Recently an extended shell around the object was discovered in IR images taken by the Spitzer Space Observatory and the WISE mission at wavelengths longer than 5 µm [22]. This finding is consistent with the idea of a past giant eruption of MWC 930.…”
Section: Discussionsupporting
confidence: 78%
“…MWC 930 was suggested as a cLBV quite long ago (Miroshnichenko et al 2005) and its LBV status was confirmed this year (Miroshnichenko et al 2014). Discovery of a circular shell around MWC 930 (Cerrigone et al 2014) lends an additional support to the LBV status of this star.…”
Section: Galactic Bona Fide Lbvsmentioning
confidence: 74%